2015
DOI: 10.1371/journal.pone.0129230
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity and Related Factors among Bouyei and Han Peoples in Guizhou Province, Southwest China

Abstract: ObjectiveTo investigate the prevalence of general and abdominal obesity and associated factors in Bouyei and Han peoples.DesignA cross-sectional study was carried out in Guizhou province, southwest China in 2012, with multi-stage sampling to enroll 4551 participants aged 20 to 80 years. General and abdominal obesity were defined by World Health Organization (WHO) for Chinese. A design-based analysis was performed to evaluate prevalence of obesity and its related factors.ResultsBouyei people had a significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
2
16
1
Order By: Relevance
“…Interestingly, in our study, the prevalence of all types of obesity (BMI≥25 kg/m 2 , obesity requiring pharmacotherapy, and BMI≥30 kg/m 2 ) in people older than 70 years was lower than in people 20 to 69 years of age, similarly to previous results [11]. Moreover, severe obesity (BMI≥30 kg/m 2 ) decreased with age in this study, implying that older people typically exhibit only mild obesity, which may be partly due to the effects of obesity-related mortality [1112]. It is well known that obesity is associated with significantly higher all-cause mortality in comparison to normal weight [1112].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, in our study, the prevalence of all types of obesity (BMI≥25 kg/m 2 , obesity requiring pharmacotherapy, and BMI≥30 kg/m 2 ) in people older than 70 years was lower than in people 20 to 69 years of age, similarly to previous results [11]. Moreover, severe obesity (BMI≥30 kg/m 2 ) decreased with age in this study, implying that older people typically exhibit only mild obesity, which may be partly due to the effects of obesity-related mortality [1112]. It is well known that obesity is associated with significantly higher all-cause mortality in comparison to normal weight [1112].…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that the overall prevalence of overweight/obesity among adults in Jiangxi Province, China was 33.7% (25.8% overweight and 7.9% obesity). Approximately one-third of the participants were either overweight or obesity, which is a relatively low prevalence compared to the prevalence in other regions of China and other developed countries [ 23 25 ]. This phenomenon may due to the cause of demographics distribution and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid changes in hormones, and physical activity levels may be responsible for this difference. Previous studies reported that living in urban areas would put the residents at a higher risk of developing abdominal obesity [ 25 ]. Our study also reported that the prevalence of abdominal obesity in urban areas was significantly greater than that in rural areas, but no association was found, which could be due to the difference in WC cut-off reference standards.…”
Section: Discussionmentioning
confidence: 99%
“…Current drinkers were defined as those who drank at least twice per month with intake of more than 640 ml (one bottle) beer or 100 ml liquor for at least 6 months and were classified into three categories: low-risk drinkers (1-40 g/d for males, 1-20 g/d for females), moderate-risk drinkers (41-60 g/d for males, 21-40 g/d for females), and high-risk drinkers (61- g/d for males, 41- g/d for females) [ 14 ]. According to the usual occupational physical activity pattern in the past year, physical activity was classified into three groups: light for sedentary office workers, shop assistants and general housework; moderate for drivers, carpenters and electrician; heavy for manual workers such as building and agricultural laborers [ 15 ].…”
Section: Methodsmentioning
confidence: 99%